2019
DOI: 10.1111/jnc.14854
|View full text |Cite
|
Sign up to set email alerts
|

Fast serotonin voltammetry as a versatile tool for mapping dynamic tissue architecture: I. Responses at carbon fibers describe local tissue physiology

Abstract: It is important to monitor serotonin neurochemistry in the context of brain disorders. Specifically, a better understanding of biophysical alterations and associated biochemical functionality within subregions of the brain will enable better of understanding of diseases such as depression. Fast voltammetric tools at carbon fiber microelectrodes provide an opportunity to make direct evoked and ambient serotonin measurements in vivo in mice. In this study, we characterize novel stimulation and measurement circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 35 publications
2
35
1
Order By: Relevance
“…Surprisingly, it was quite easy to give adjustments for a small number of parameters (Table 5 ) that distinguish between fast, slow, and hybrid responses. First, we raised the of SERT from 250 to 433 and this lowered the steady-state value of eht from 60 nM to 39.8 nM consistent with the measurements in [ 60 ]. Note that the slope of the slow parts of the experimental curves (red dots) in Fig.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…Surprisingly, it was quite easy to give adjustments for a small number of parameters (Table 5 ) that distinguish between fast, slow, and hybrid responses. First, we raised the of SERT from 250 to 433 and this lowered the steady-state value of eht from 60 nM to 39.8 nM consistent with the measurements in [ 60 ]. Note that the slope of the slow parts of the experimental curves (red dots) in Fig.…”
Section: Resultssupporting
confidence: 82%
“…The distribution is broad with a range of 45 to 70 nM, a mean of 58.7 nM and a standard deviation of 4.3 nM. This distribution is similar to the distributions seen in the pre-frontal cortex of mice in the Hashemi Lab [ 60 ]. For no autoreceptors, the distribution is given by the pink bars in Fig.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Uptake 2 occurs as a result of non-SERT transporters and is characterized by higher 5 22 efficiency, but lower capacity and affinity. Studies in mice have shown that Uptake 2 has a much shorter decay curve that reaches baseline activity quickly(Abdalla et al, 2019). These studies 5 have further suggested that serotonin release in the hippocampus is largely mediated by Uptake5 2 (non-SERT) mechanisms (West et al, 2018; Abdalla et al, 2019).…”
mentioning
confidence: 99%